Agamermis sp. (Nematoda: Mermithidae) parasitizing Armadillidium vulgare (Crustacea: Isopoda) in Argentina - Rusconi, Jose Matias (2023)
The Mermithidae is a family of nematodes parasitic in many kinds of insects, spiders, leeches, crustaceans and other invertebrates throughout the world. While conducting an assay with entomopathogenic nematodes, we found Armadillidium vulgare (Crustacea: Isopoda) individuals to be infected with Agamermis sp., marking the fourth known discovery of a mermithid infection in the order Isopoda. In this work, we contribute with an 18S rDNA sequence of the isolated nematode and the morphological and morphometrical characterization of the juveniles.